Pola Pengeluaran Rumah Tangga Tani Padi Pemilik Penggarap di Desa Ngengor, Kecamatan Pilangkenceng, Kabupaten Madiun - Fardani, Aprissa Ega; Yuliati, Nuriah; Syah, Mirza Andrian (Universitas Galuh, 2025)
The agricultural sector has a large contribution to the Indonesian economy, but rice farmers are still less prosperous. This condition raises questions about the economic conditions of farmers who have limited land, especially in Ngengor Village, Pilangkenceng District, Madiun Regency. The purpose of this study was to identify the expenditure patterns of farming households and analyze the factors that influence farming household expenditure. This study was conducted on 54 farming households using the simple random sampling method. Data were analyzed using descriptive statistics and multiple linear regression analysis. The results showed that the average household expenditure per year reached IDR 20,345,474, with a distribution between food needs (53.58%) and non-food (46.42%). Income, education level (elementary, junior high, and high school), and number of family members have a significant effect on household expenditure. Meanwhile, land area does not have a significant effect. The results of this study highlight the importance of income and education in the financial management strategy of farming households, as well as the importance of diversifying sources of income for small-scale farming households